The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/brs.0b013e31818b9029
|View full text |Cite
|
Sign up to set email alerts
|

Face Tissue Pressure in Prone Positioning

Abstract: The Dupaco ProneView Protective Helmet System is superior to both the OSI and the ROHO positioners in decreasing forehead and chin tissue interface pressures during prone position surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…3,21 The risk increases with longer duration and increased volume replacement causing increased facial edema. 21 Pressure on the face in prone position is on average 30 mmHg, but can be higher than 50 mmHg in certain areas such as the chin and forehead above the supraorbital ridge.…”
Section: Head and Neck Pressure Soresmentioning
confidence: 99%
See 1 more Smart Citation
“…3,21 The risk increases with longer duration and increased volume replacement causing increased facial edema. 21 Pressure on the face in prone position is on average 30 mmHg, but can be higher than 50 mmHg in certain areas such as the chin and forehead above the supraorbital ridge.…”
Section: Head and Neck Pressure Soresmentioning
confidence: 99%
“…The rate of this complication is estimated to be between 0.05% and 1%. 3,21,22,31 Ischemic optic neuropathy (ION) and orbital compartment syndrome (OCS) Direct pressure on orbits can cause trauma resulting in conjunctival edema, hemorrhage, chemosis, pain, and vision loss. 7,14 ION is caused by damage to optic nerve by increased intraocular pressure and orbital venous pressure.…”
Section: Postoperative Vision Loss (Povl) and Other Ophthalmic Injuriesmentioning
confidence: 99%
“…Grisell and Place compared the amount of facial pressure on each of the three types of face positioners: the OSI foam positioner (the one used in our patients), Protective Helmet system that uses a disposable polyurethane foam head positioner (Dupaco Inc., Oceanside, CA, USA), and a neoprene air-filled bladder “dry floatation” device by ROHO (The ROHO Group, Belleville, IL, USA). [ 7 ] They observed that tissue pressures seemed equal within the first 15 min and then remained fairly constant. The pressures measured for the Dupaco positioner were lowest at all time points for both the forehead and the chin in comparison to the other two positioners.…”
Section: Discussionmentioning
confidence: 99%
“…These injuries, though seem trivial in nature most of the time, can act as a nidus for infection requiring protracted hospital stay or even surgical intervention occasionally, ultimately leading to increased morbidity and health-care cost. [ 7 ] The nonmonetary costs related to these skin breakdowns include pain, infection, consumption of additional hospital resources, and emotional and physical effects on patients and their caregivers. [ 8 9 ] Reported rates of pressure-related skin ulcers from prone position surgery vary from 5% to 66%.…”
Section: Introductionmentioning
confidence: 99%
“…A study of facial tissue pressures in the prone position revealed that pressure effects can be reduced by careful selection of an appropriate head rest, with a polyurethane foam head rest within a protected helmet system advocated [13]. Möllmann and colleagueshave advocated for a transparent operating table with a foam-cushion face mask to facilitate intraoperative monitoring [14].…”
Section: Discussionmentioning
confidence: 99%